Sleep Disorders: Is the Trigemino-Cardiac Reflex a Missing Link? - Chowdhury, Tumul; Bindu, Barkha; Singh, Gyaninder Pal; Schaller, Bernhard (Frontiers in Neurology, 2017)
Abstract Trigeminal innervated areas in face, nasolacrimal and nasal mucosa can produce a wide array of cardio-respiratory manifestations that include apnea, bradypnea, bradycardia, hypotension, and arrhythmias. This reflex is a well-known entity called 'trigemino-cardiac reflex.' (TCR). The role of TCR is investigated in various pathophysiological conditions especially in neurosurgical, but also skull base surgery procedures. Additionally, its significance in various sleep related disorders has also been highlighted recently. Though, the role of diving reflex, a subtype of TCR, has been extensively investigated in sudden infant death syndrome. The data related to other sleep disorders including obstructive sleep apnea, bruxism is very limited and thus, this review aims to investigate the possible role and correlation of TCR in causing such sleep abnormalities.